THE ANALYSIS OF ENERGY BEHAVIOR OF ENVIRONMENTALLY INSIGHT COMMUNITY - Irwan Syarif; Hamsu Abdul Gani; Nurlita Pertiwi; Andi Nur Putri; Muh. Rais (International Conference on Social and Islamic Studies, 2021)
The increasing consumption of electrical energy coupled with the dwindling availability of fossil energysources has resulted in a world energy crisis, especially in Indonesia. The government has begun to takesolution steps to save the world's energy, such as policies to use renewable energy as alternative energyand energy conservation. The purpose of this study is to identify the energy-saving behavior of thecommunity as a step to follow government regulations regarding the implementation of energyconservation. By using a quantitative approach, this study also aims to determine what factorsencourage a person to consume electrical energy that is environmentally sound. Environmentally soundenergy behavior is expected to be one of the solutions in solving the problem of the world energy crisisin addition to the use of renewable energy as alternative energy and a benchmark for public awarenessof energy problems.